Wandering Jews Global Jewish Migration - Gold, Steven J. (Purdue University Press, 2020)
Despite the importance of historical and contemporary migration to the American Jewish community, popular awareness of the diversity and complexity of the American Jewish migration legacy is limited and largely focused upon Yiddish-speaking Jews who left the Pale of Settlement in Eastern Europe between 1880 and 1920 to settle in eastern and midwestern cities. Wandering Jews provides readers with a broader understanding of the Jewish experience of migration in the United States and elsewhere. It describes the record of a wide variety of Jewish migrant groups, including those encountering different locations of settlement, historical periods, and facets of the migration experience. While migrants who left the Pale of Settlement in the late nineteenth and early twentieth centuries are discussed, the volume's authors also explore less well-studied topics. These include the fate of contemporary Jewish academics who seek to build communities in midwestern and western college towns; the adaptation experience of recent Jewish migrants from Latin America, Israel, and the former Soviet Union; the adjustment of Iranian Jews; the experience of contemporary Jewish migrants in France and Belgium; the return of Israelis living abroad; and a number of other topics. Interdisciplinary, the volume draws upon history, sociology, geography, and other fields. Written in a lively and accessible style, Wandering Jews will appeal to a wide range of readers, including students and scholars in Jewish studies, international migration, history, ethnic studies, and religious studies, as well as general-interest readers.